Comparing recent and preindustrial cladoceran assemblages in 35 metal- and smelting-affected lakes near Sudbury (Ontario, Canada). (24th February 2022) - Simmatis, Brigitte; Paterson, Andrew M; Smol, John P
Abstract: Base metal smelting activity around Sudbury (Ontario, Canada) has persisted for over a century, emitting metals and acidifying contaminants that affected lakes downwind of smelter stacks. Although considerable research has been directed toward the paleolimnological study of diatoms and chrysophytes in the region, relatively little comparable work has been completed on invertebrates. Here, cladoceran (Branchiopoda: Cladocera) assemblages are compared using a paleolimnological "top-bottom approach", comparing preimpact and recent assemblages. Spatiotemporal differences were likely driven by acidification-related stressors and legacy effects of metal contamination. The replacement of the Daphnia longispina complex with the Daphnia pulex complex is attributable to diminished lake-water calcium concentrations. Increased abundances of early colonist taxa demonstrate that many acidified lakes have not fully recovered. Regional stressors further complicate recovery and the interpretation of temporal changes. Finally, clustering of recent cladoceran assemblages reflects the effects of modern multiple stressors and persistent historical stressors. This study shows that acidification history partially explains differences in cladoceran assemblages, but also that multiple stressors will likely continue to influence assemblage composition and recovery in Sudbury lakes. Defining appropriate reference conditions, considering historical and modern stressors, will be important when assessing the extent and trajectory of ecosystem recovery from widespread anthropogenic impacts.